Valuation of environmental management standard ISO 14001: Evidence from an emerging market - Hammad Riaz; Abubakr Saeed; Muhammad Saad Baloch; Nasrullah Khan; Zeeshan Ahmad Khan (Journal of Risk and Financial Management, 2019)
ISO 14001 (Environmental Management Standard) helps corporations to build legitimacy and goodwill, and can be also viewed as an organizational response to institutional pressure to act proactively towards the environment. The purpose of this paper is to investigate how investors in the emerging country value voluntary environmental management standard ISO 14001 certification. The impact of voluntary environmental management standard ISO 14001 on market performance is still not clear. By using event study methodology, this study matched ISO-certified firms with non-certified ones based on three different matching principles that include return on assets, size, and industry. The findings indicated that investors negatively valued ISO 14001 in both the short and long run. The study recommended policy implications for managers, policy makers, and non-government organizations.
Keywords: 330; ISO 14001; legitimacy; institutional forces; environmental system; event study approach; emerging markets